Subculture of Germ Cell-Derived Colonies with GATA4-Positive Feeder Cells from Neonatal Pig Testes. (6th January 2016) - Lee, Kyung Hoon; Lee, Won Young; Kim, Jin Hoi; Park, Chan Kyu; Do, Jeong Tae; Kim, Jae Hwan; Choi, Young Suk; Kim, Nam Hyung; Song, Hyuk
Abstract : Enrichment of spermatogonial stem cells is important for studying their self-renewal and differentiation. Although germ cell-derived colonies (GDCs) have been successfully cultured from neonatal pig testicular cells under 31°C conditions, the short period of in vitro maintenance (<2 months) limited their application to further investigations. To develop a culture method that allows for in vitro maintenance of GDCs for long periods, we subcultured the GDCs with freshly prepared somatic cells from neonatal pig testes as feeder cells. The subcultured GDCs were maintained up to passage 13 with the fresh feeder cells (FFCs) and then frozen. Eight months later, the frozen GDCs could again form the colonies on FFCs as shown in passages 1 to 13. Immunocytochemistry data revealed that the FFCs expressed GATA-binding protein 4 (GATA4), which is also detected in the cells of neonatal testes and total testicular cells, and that the expression of GATA4 was decreased in used old feeder cells. The subcultured GDCs in each passage had germ and stem cell characteristics, and flow cytometric analyses revealed that 60% of these cells were GFR α -1 positive. In conclusion, neonatal pig testes-derived GDCs can be maintained for long periods with GATA4-expressing testicular somatic cells.